Invasion status of the common carp Cyprinus carpio in inland waters of Argentina - Maiztegui, Tomás (2016)
This study documents the presence of Cyprinus carpio in 119 natural environments and 49 artificial habitats in Argentina, showing an exponential increment of invaded locations over time since it was introduced in the nineteenth century. Geographic expansion patterns revealed that since its initial introduction, species records demonstrate an increment in the central portion of the country only after 1970 and subsequent expansion after 1990 to the north, west and south. Using an environmental similarity index it was determined that more than half the country offers good conditions for C. carpio establishment. Environmental factors and anthropogenic impacts are relevant drivers that can account for the current and future distribution of C. carpio in Argentina.